Brain Switches Utilitarian Behavior: Does Gender Make the Difference? - Fumagalli, Manuela; Vergari, Maurizio; Pasqualetti, Patrizio; Marceglia, Sara; Mameli, Francesca; Ferrucci, Roberta; Mrakic-Sposta, Simona; Zago, Stefano; Sartori, Giuseppe; Pravettoni, Gabriella; Barbieri, Sergio; Cappa, Stefano; et al. (PloS one, 2010)
Decision often implies a utilitarian choice based on personal gain, even at the expense of damaging others. Despite the social implications of utilitarian behavior, its neurophysiological bases remain largely unknown. To assess how the human brain controls utilitarian behavior, we delivered transcranial direct current stimulation (tDCS) over the ventral prefrontal cortex (VPC) and over the occipital cortex (OC) in 78 healthy subjects. Utilitarian judgment was assessed with the moral judgment task before and after tDCS. At baseline, females provided fewer utilitarian answers than males for personal moral dilemmas (p = .007). In males, VPC-tDCS failed to induce changes and in both genders OC-tDCS left utilitarian judgments unchanged. In females, cathodal VPC-tDCS tended to decrease whereas anodal VPC-tDCS significantly increased utilitarian responses (p = .005). In males and females, reaction times for utilitarian responses significantly decreased after cathodal (p<.001) but not after anodal (p = .735) VPC-tDCS. We conclude that ventral prefrontal tDCS interferes with utilitarian decisions, influencing the evaluation of the advantages and disadvantages of each option in both sexes, but does so more strongly in females. Whereas cathodal tDCS alters the time for utilitarian reasoning in both sexes, anodal stimulation interferes more incisively in women, modifying utilitarian reasoning and the possible consequent actions. The gender-related tDCS-induced changes suggest that the VPC differentially controls utilitarian reasoning in females and in males. The gender-specific functional organization of the brain areas involved in utilitarian behavior could be a correlate of the moral and social behavioral differences between the two sexes.